Lipoprotein(a) and cardiovascular disease: prediction, attributable risk fraction and estimating benefits from novel interventions. (25th November 2020) - Welsh, P; Welsh, C; Celis-Morales, C.A.C; Brown, R; Ferguson, L.D; Gray, S; Mark, P; Lewsey, J; Lyall, D.M; Gill, J.M.R; Pell, J; Jhund, P.S; et al.
Abstract: Background: Lipoprotein (a) (Lp(a)) measurement may help guide CVD risk prediction, is thought to be causal in several CVD outcomes, and phase 3 intervention trials of Lp(a) lowering agents are underway. We aimed to investigate the population attributable fraction due to elevated Lp(a) and its utility in CVD risk prediction. Methods: In 413, 724 participants from UK Biobank, associations of serum Lp(a) with composite fatal/nonfatal CVD (n=10, 065 events), fatal CVD (n=3247), coronary heart disease (n=16, 649), ischaemic stroke (n=3191), and peripheral vascular disease (n=2716) were compared using Cox models. Predictive utility was determined by C-index changes. The population attributable fraction was estimated. Results: Median Lp(a) was 19.7nmol/L (interquartile interval 7.6–75.3nmol/L). 20.8% had Lp(a) values >100nmol/L; 9.2% had values >175nmol/L. After adjustment for classical risk factors, in participants with no baseline CVD and not taking a statin, 1 standard deviation increment in log Lp(a) was associated with a HR for fatal/nonfatal CVD of 1.09 (95% CI 1.07–1.11). Associations were similar for fatal CVD, coronary heart disease, and peripheral vascular disease. Adding Lp(a) to a prediction model containing traditional CVD risk factors improved the C-index by +0.0017 (95% CI 0.0009, 0.0026). We estimated that having Lp(a) values >100nmol/L accounts for 5.7% of CVD events in the whole cohort. We modelled that an ongoing trial to lower Lp(a) in patients with CVD and Lp(a) above ∼175nmol/L may be expected to reduce CVD risk by 20.3%, assuming causality, and an achieved Lp(a) reduction of 80%. Conclusions: Population screening for elevated Lp(a) may help to predict CVD and target Lp(a) lowering drugs to those with markedly elevated levels, if such drugs prove efficacious. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Chest, Heart, and Stroke Association Scotland and British Heart Foundation